1997
DOI: 10.1038/eye.1997.138
|View full text |Cite
|
Sign up to set email alerts
|

Development of exudative age-related macular degeneration after cataract surgery

Abstract: The macular status of patients with findings consistent with early dry age-related macular degeneration (AMD) who underwent an extracapsular cataract extraction with intraocular lens implantation was evaluated by fundoscopy and fluorescein angiography pre-operatively and during the first post-operative year. Five patients who developed the exudative form of AMD, and who represent the problems arising when treating patients with AMD and cataract, are described. Patients who received laser photocoagulation respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…However, studies of the effect of cataract surgery on the progression of AMD are inconclusive, and many relate to older techniques of cataract surgery and IOL designs. Within the first year after cataract surgery, Pollack et al 7,8 found an increased rate of progression over that in the fellow unoperated eye. Kaiserman et al 9 report an increased need for photodynamic therapy for choroidal neovascular complex leakage within 6 months and 12 to 18 months after cataract surgery.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies of the effect of cataract surgery on the progression of AMD are inconclusive, and many relate to older techniques of cataract surgery and IOL designs. Within the first year after cataract surgery, Pollack et al 7,8 found an increased rate of progression over that in the fellow unoperated eye. Kaiserman et al 9 report an increased need for photodynamic therapy for choroidal neovascular complex leakage within 6 months and 12 to 18 months after cataract surgery.…”
Section: Discussionmentioning
confidence: 97%
“…The removal of the cataract in patients with AMD and implantation of a colorless lens (blocking only UV light) would increase the exposure of already degenerating RPE cells to blue light and may boost their deterioration and their loss of functional viability [35][36][37]. One may hypothesize that the implantation of a yellow-tinted lens that mimics the color of the natural lens would reduce the risk of blue-light exposure.…”
Section: Discusionmentioning
confidence: 97%
“…Although earlier case series [6][7][8][9] and a postmortem study 10 suggested a possible association between aphakia or pseudo-phakia and late ARM, the evidence from these studies is relatively weak. Findings from large population-based studies 11,12 appeared to support an association between prior cataract surgery and an increase in late ARM prevalence.…”
Section: Introductionmentioning
confidence: 98%
“…The strongest evidence to date, came from a pooled data analysis of two large populationbased studies, 13 that showed a significantly increased 5-year incidence of late ARM (odds ratio (OR) 5.7, 95% confidence interval (CI) 2.4-13.6) in nonphakic (aphakic or pseudo-phakic) eyes compared to phakic eyes, after accounting for age, smoking, and the presence and severity of early ARM lesions at baseline. 13 The Beaver Dam Eye Study (BDES) has reported a significant association between cataract surgery performed prior to baseline and the incidence of late ARM after both [5][6][7][8][9][10][11][12][13][14] and 10-year 15 intervals. The potential for an increased late ARM risk after cataract surgery remains topical and controversial, as indicated by two recent editorials published in Archives of Ophthalmology.…”
Section: Introductionmentioning
confidence: 99%